1992
DOI: 10.3406/spgeo.1992.3079
|View full text |Cite
|
Sign up to set email alerts
|

La mine, élément de la controverse écologique dans le Pacifique Sud

Abstract: Mines: an element of the ecological debate in the South Pacific. — The island of Nauru, Grande Terre in New Caledonia and Bougainville in Papua-New Guinea have open air mines ranking among the most extensive world-wide, of phosphates, nickel and copper respectively. The exploitation of the mines has caused major disturbances in the natural and social environment of neighbouring populations. In two cases out of three, such disturbances, in the late 1960s and early 1970s, stemmed from the fact that natural, huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Moreover, visual observations, colorimetric and geochemical analyses indicated a modification of sediment composition during this phase resulting in the dominance of red-coloured, nickel and goethite/hematite-enriched sediment. This red coloration of sediment described in the studies (Bird et al, 1984;Iltis, 1992) but also observed in the sediment core could correspond to the release of laterites initially stored on the foothills.…”
Section: Periods 2 and 3 From 1950 To 1989: The Mechanization Of Mining Activities From A Non-regulated Extraction To The First Environmementioning
confidence: 53%
See 3 more Smart Citations
“…Moreover, visual observations, colorimetric and geochemical analyses indicated a modification of sediment composition during this phase resulting in the dominance of red-coloured, nickel and goethite/hematite-enriched sediment. This red coloration of sediment described in the studies (Bird et al, 1984;Iltis, 1992) but also observed in the sediment core could correspond to the release of laterites initially stored on the foothills.…”
Section: Periods 2 and 3 From 1950 To 1989: The Mechanization Of Mining Activities From A Non-regulated Extraction To The First Environmementioning
confidence: 53%
“…Indeed, the rapid increase of nickel ore production was accompanied by a sharp increase in mining waste (i.e. 2.1 tons per tons of nickel ore mined; Iltis (1992); Figure 5), resulting in an increase of sediment inputs to the New Caledonian rivers (Bird et al, 1984;Iltis, 1992).…”
Section: Periods 2 and 3 From 1950 To 1989: The Mechanization Of Mining Activities From A Non-regulated Extraction To The First Environmementioning
confidence: 99%
See 2 more Smart Citations
“…New Caledonia, an island located in the south-western Pacific Ocean and currently the world's sixth-largest producer of nickel, is in particular challenged with the problems of hyper-sedimentation and over-burden of its river systems. Several studies outline how mining activities, which started in 1875, are generally responsible for these deleterious river morphological changes (Bird et al, 1984;Iltis, 1992;Garcin et al, 2017). The excessive sediment inputs transferred mainly during extreme rainfall events (e.g.…”
Section: Introductionmentioning
confidence: 99%